2018
DOI: 10.1681/asn.2017111225
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Arteriovenous Fistula Clinical Maturation from Postoperative Ultrasound Measurements: Findings from the Hemodialysis Fistula Maturation Study

Abstract: Background The utility of early postoperative ultrasound measurements in predicting arteriovenous fistula (AVF) clinical maturation is uncertain. Methods We investigated the relationships of ultrasound parameters with AVF clinical maturation in newly created AVF, measured at 1 day and 2 and 6 weeks, in 602 participants of a multicenter, observational cohort study. A backward elimination algorithm identified ultrasound measurements that independently predicted unassisted and overall AVF maturation. Candidate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
96
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 39 publications
3
96
0
5
Order By: Relevance
“…A prediction model including AVF blood flow, diameter, and depth at 1 day and 2 and 6 weeks after AVF placement achieved C statistics of 0.69, 0.74, and 0.79, respectively, for unassisted maturation and 0.69, 0.71, and 0.76, respectively, for overall AVF maturation. Patient's case‐mix factors including age, gender, race, dialysis status, diabetes, BMI, and AVF location (forearm versus upper arm) were not associated with unassisted or overall AVF maturation . We highly recommend future studies to further evaluate these parameters for possibilities to include ultrasound evaluation as a routine clinical practice.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A prediction model including AVF blood flow, diameter, and depth at 1 day and 2 and 6 weeks after AVF placement achieved C statistics of 0.69, 0.74, and 0.79, respectively, for unassisted maturation and 0.69, 0.71, and 0.76, respectively, for overall AVF maturation. Patient's case‐mix factors including age, gender, race, dialysis status, diabetes, BMI, and AVF location (forearm versus upper arm) were not associated with unassisted or overall AVF maturation . We highly recommend future studies to further evaluate these parameters for possibilities to include ultrasound evaluation as a routine clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…A larger proportion of matured AVF were abandoned in females (21%) than in males (16% with unassisted or overall AVF maturation. 11 We highly recommend future studies to further evaluate these parameters for possibilities to include ultrasound evaluation as a routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 602 fistulas suggested that low blood flow and a small venous diameter at 2 weeks are predictive of AVFs that may not develop optimally at 6 weeks . A follow‐up evaluation of the 602 AVFs showed that measurement of the AVF blood flow rate, AVF diameter, and distance of the anterior AVF vein wall from the skin was moderately predictive of AVF maturation . A separate study showed an increased risk of failure to mature if blood flow was less than 413 mL/min at 2 weeks after fistula creation …”
Section: Specifications Of the Examinationmentioning
confidence: 99%
“…If no stenosis is identified, thresholds for the AVF vein diameter and blood flow and AVF depth from the skin may suggest whether the AVF is adequately mature for hemodialysis . An AVF with a venous diameter of at least 0.4 to 0.6 cm and blood flow of at least 500 to 600 mL/min predicts that an AVF has a high likelihood of supporting successful hemodialysis .…”
Section: Specifications Of the Examinationmentioning
confidence: 99%
“…Results from the Haemodialysis Fistula Maturation (HFM) study are expected to advance our understanding of anatomical, biological and clinical characteristics, as well as processes of care associated with enhanced AVF usability254 . This study has recruited 602 patients undergoing single-stage AVF surgery in the US and already provided information on clinical and post-operative processes of care predictors of AVF maturation255,256 . Assessment of pre-operative vessel characteristics, anaesthetic (e.g.…”
mentioning
confidence: 99%